Transnational Constitutional Law: Bridging National Constitutions with International Norms: Transnational Constitutional Law: Bridging National Constitutions with International Norms - Andi Widjaja; Abdul Latif; Alan Robert White (PENA LAW: International Journal of Law, 2026)
This article examines the role of transnational constitutional law as a framework for linking national constitutions with international legal norms in an era of growing global legal interdependence. While traditional theories of monism and dualism have long shaped discussions about how national and international law relate, this research shows that these models are insufficient to reflect the complex realities of modern constitutional practice. Using a normative juridical and comparative qualitative approach, the study analyzes constitutions, international treaties, and constitutional court decisions as primary sources, supported by scholarly literature and institutional reports. The findings identify three main interaction patterns: normative convergence, where international norms are integrated to bolster domestic constitutional legitimacy; constitutional resistance, where states prioritize sovereignty and selectively adopt international standards; and hybrid models, where courts navigate between domestic and international obligations through doctrines such as the margin of appreciation. These patterns underscore the increasing importance of constitutional pluralism, which views the relationship between national and international law as dialogical rather than hierarchical. Extending the analysis beyond Eurocentric contexts, this article highlights perspectives from the Global South, especially Indonesia, where selective adoption of international norms illustrates the constitutional balancing act between national identity and global commitments.